Short and long-term differences in anthropometric characteristics and physical performance between male rugby players that became professional or remained amateur - Hamlin, M. J.; Deuchrass, R. W.; Elliot, C. E.; Manimmanakorn, N. (Journal of Exercise Science & Fitness, 2021)
Objective: The objective of this study was to investigate which anthropometric and physical performance variables characterised players that advanced to professional teams (professionals) and how these variables changed over time, compared to those that did not secure professional contracts (i.e. remained amateurs). Methods: Differences in anthropometry, strength, speed, power and intermittent running ability in 83 male rugby players collected between 2015 and 2019 were determined using repeated measures analysis. Results: When arriving for the first year of the program, forwards that went on to become professional players were older (0.4 ± 0.3 yr, mean ± 95% CI, p = 0.004), heavier (4.6 ± 2.5 kg, p < 0.001) and stronger (range 6.2-16.4%) than forwards that remained amateur. Professional forwards were also slower at sprinting (range -2.7-2.9%, p < 0.001) and had lower Yo-Yo IRT L1 (-10.8%, p = 0.03). When first arrived on the program, professional backs were taller (3.5 ± 1.8 cm, p < 0.001), heavier (4.6 ± 2.4 kg, p < 0.001) and faster over 20 m (-1.9 ± 1.7%, p = 0.03) and 30 m (-1.7 ± 1.6%, p = 0.04) compared to amateurs. Compared to amateurs, professionals had a smaller increase in body mass (-4.2 ± 2.0%, p < 0.001) and greater improvement in sprinting (3.7, 2.8, 2.8% over 10, 20 and 30-m, respectively) and Yo-Yo IRT L1 (14.7 ± 11.0%, p = 0.05) over 3 years training. Conclusion: Characteristics that are likely to assist players in becoming professionals include being older, heavier, taller and stronger.